Semiotics of communication in kazakh literature (Journal of Philosophy Culture and Political Science, 2018)
The article presents the analysis of communication semiotics in traditional Kazakh culture. The authors depict the image of the exemplary person making the review of communication cultural change begun in the Kazakh khanate and their symbolic descriptions. The formation of a special ethno-sociological consciousness of the sociological communication and sociological trends of a single culture in the Kazakh steppe is reasoned by creativity of poets, zhyrau and writers.Key words: Kazakh culture, tradition, communication, symbols, worldview, way.